2019
DOI: 10.1055/s-0039-3400986
|View full text |Cite
|
Sign up to set email alerts
|

Early Treatment in Acute Severe Encephalopathy Caused by ATP1A2 Mutation of Familial Hemiplegic Migraine Type 2: Case Report and Literature Review

Abstract: Familial hemiplegic migraine type 2 (FHM2) is an autosomal dominant inheritance disorder caused by ATP1A2 mutation, and the clinical spectrum is heterogeneous even with acute severe encephalopathy. However, up to now, early treatments against acute and severe attacks in FHM2 are still insufficient. Here, we report a 15-year-old female with intellectual disability due to FHM2 caused by a pathogenic ATP1A2 gene mutation, presenting mild-to-moderate headache at the onset, followed by confusion, complete right hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…As a rare kind of migraine with aura, HM with ATP1A2 gene mutation is described in only a few case reports. Some scholars have summarized the clinical characteristics of HM with ATP1A2 mutation [1,3,6,8]. In the present case, excessive food intake was the only trigger.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…As a rare kind of migraine with aura, HM with ATP1A2 gene mutation is described in only a few case reports. Some scholars have summarized the clinical characteristics of HM with ATP1A2 mutation [1,3,6,8]. In the present case, excessive food intake was the only trigger.…”
Section: Discussionmentioning
confidence: 65%
“…Similar to previous reports, in the present case, the patient's CSF pressure, hematological and biochemical analysis were all normal. Although there have been previous case reports about the use of acyclovir [6,8,10,13,14], we believed that the patient's fever and coma were clinical manifestations of this type of HM, rather than viral encephalitis, and did not use any antiviral treatment. Thus, antiviral treatment is not recommended in the absence of de nitive markers of intracranial infection.…”
Section: Discussionmentioning
confidence: 81%
“…The symptoms commonly observed in individuals with FHM include reversible visual, sensory, or language disturbances, as well as varying degrees of limb hemiplegia ( 13 ). Some individuals with FHM who possess a mutation in the ATP1A2 gene have experienced severe attacks characterized by recurrent coma, fever, and/or epileptic seizures ( 13 , 14 ). It is plausible to consider that the viral encephalitis and seizures diagnosed in the boy at the age of 5 may represent a manifestation of the severe acute encephalopathy associated with this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several neuropsychological studies have demonstrated that focal and degenerative cerebellar disorders associated with FHM can result in significant cognitive impairments ( 19 ). Furthermore, individuals with FHM2 may exhibit severe forms of intellectual disability ( 14 , 19 ). Additionally, investigations have revealed that mutations in all three FHM genes have the potential to cause epilepsy, with ATP1A2 mutations being particularly prevalent ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in ATP1A2 are the primary genetic cause of family hemiplegic migraine 2 (FHM2) (Du et al, 2020) and alternating hemiplegia of childhood 1 (AHC1) (Monteiro et al, 2020) . Epilepsy is described as a comorbidity of FHM2 and AHC1 in ATP1A2mutated cases (Costa et al, 2014;Deprez et al, 2008;Pisano et al, 2013).…”
Section: Introductionmentioning
confidence: 99%